Peer Social Support and Resilience as Determining Factors of Academic Burnout in College Students - Puspaningrum, Ananda Eka; Ruby, Arcivid Chorynia (Universitas Negeri Semarang, 2024)
Academic burnout is a significant issue among students, characterized by emotional exhaustion, depersonalization, and feelings of incompetence in academic tasks, often caused by chronic stress. The relevance of this issue is highlighted by the role of peer social support and resilience as independent variables influencing academic burnout. This study aims to evaluate the relationship between peer social support and resilience on academic burnout among students. The research sample consisted of 381 students selected through quota sampling. Data were collected using Likert scales, including scales for academic burnout, peer social support, and resilience. The analysis results show a correlation coefficient rx12y of 0.354 with a significance of 0.001 (p<0.01), and an effective contribution of 12.5%, indicating a significant relationship between peer social support and resilience on academic burnout. Further analysis shows that peer social support has a significant positive correlation with academic burnout (rx1y = 0.348, p<0.01), while resilience does not show a significant relationship with academic burnout (rx2y = 0.134, p>0.05). In conclusion, peer social support is significantly associated with academic burnout, while resilience does not have a significant impact. These results indicate that academic pressure and heavy workloads influencing academic burnout. Additionally, social pressure and competition within the educational system can also affect the levels of academic burnout. Universities need to develop intervention programs that not only focus on social support and resilience but also on stress and time management skills for their students.